Hybrid Short-Term Wind Power Prediction Based on Markov Chain - Zhou, Liangsong; Zhou, Xiaotian; Liang, Hao; Huang, Mutao; Li, Yi (Frontiers in Energy Research, 2022)
This article proposes a combined prediction method based on the Markov chain to realize precise short-term wind power predictions. First, three chaotic models are proposed for the prediction of chaotic time series, which can master physical principles in wind power processes and guide long-term prediction. Then, considering a mechanism switching between different physical models via a Markov chain, a combined model is constructed. Finally, the industrial data from a Chinese wind farm were taken as a study case, and the results validated the feasibility and superiority of the proposed prediction method.